Sinonasal cancer in The Netherlands: Follow‐up of a population‐based study 1989‐2014 and incidence of occupation‐related adenocarcinoma. Issue 11 (15th October 2018) - Kuijpens, J. (Hans) L. P.; Louwman, Marieke W. J.; Takes, Robert; Slootweg, Piet J.; Burdorf, Alex; van Dijk, Boukje A. C.
Abstract: Background: Long‐term trends of sinonasal cancer in The Netherlands have been investigated with particular attention on adenocarcinoma for which wood or leather dust is a well‐known risk factor. Methods: All 4345 patients (1989‐2014) registered in the Netherlands Cancer Registry were included. Standardized 3‐year moving incidence rates per 1 000 000/person‐years, and estimated annual percentage change (EAPC) were calculated. Results: Forty‐seven percent of the patients had squamous cell carcinoma (SCC), 12% had lymphoma, and 12% had adenocarcinoma. Sixty‐one percent of the tumors were located in the nasal cavity, 22% in the maxillary, and 11% in the ethmoidal sinus. Male incidence decreased to 11.5/1 000 000 due to less SCC (EAPC −0.9%; 95% confidence interval [CI] −1.6 to 0.3) and adenocarcinoma (EAPC −4.3%; 95% CI −5.5 to 3.1). Female incidence increased to 7/1 000 000 (EAPC +2.0%; 95% CI +1.1 to +3.0) due to more SCC (EAPC +2.2%; 95% CI +1.0 to +3.5), whereas adenocarcinoma remained stable (0.6/1 000 000; EAPC +1.1%; 95% CI −6.0 to +8.7). Tumors of the nasal cavity increased in women (EAPC +3.3%; 95% CI +2.0 to 4.7). Conclusion: The decrease of male sinonasal adenocarcinoma may be the result of preventive measures combined with less workers in high‐risk occupations.